Staff Expectancies in Conducting Ship Hygiene and Sanitation Inspections: A Qualitative Study at Banten Class I Port Health Quarantine Office - Waris, Lukman; Budiman, Budiman; Aryani, Hany Puspita (UI Scholars Hub, 2025)
Sea transport plays a vital role in the movement of goods and passengers, yet it simultaneously poses a potential risk for the transmission of infectious diseases, both nationally and internationally. Ship hygiene and sanitation inspection (HSI) is a strategic measure to control such risks, and the outcomes of these inspections are influenced by the expectations of the implementing officers. This study explores how staff expectancy at the Banten Class I Port Health Quarantine Office affects the quality of HSI. A qualitative study using the Rapid Assessment Procedure (RAP) was conducted with 80 staff members across five work units. Data were collected through in-depth interviews, focus group discussions, and field observations, and analyzed using triangulation of sources and methods. Findings indicate that expectancy is shaped by perceived ability, work experience, and technical skills, all of which affect motivation and inspection quality of HSI. Officers with high expectancy demonstrated stronger motivation and performance, while limited experience and competency hindered those with lower expectancy. This study recommends strengthening staff capacity through continuous training, establishing multidisciplinary inspection teams, and enhancing institutional support through performance-based incentives. The findings highlight staff expectancy as a critical factor in improving the quality of HIS.